Model Supply Chain Management Dalam Upaya Pengembangan Industri Batik Tulis Lasem Kabupaten Rembang - Muhammad Tahwin; A. Aviv Mahmudi; Dian Ayu Liana Dewi (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2016)
Supply Chain management is business process system used to manage planning started from process of acquiring basic material until finished product got by the consumers. The problem occurs is  how the industrialist in supply chain able to distribute the product related to  just in time concept. Such as Batik Tulis Lasem Industry which still faces the problem about applying supply chain model. All this time  is still based on a going custom.  This research aim is to produce appropriate supply chain for characteristic and  condition of Batik Tulis Lasem Industry. Analysis data used is descriptive analysis. The research result is managing basic material properly has important role in developing Batik Tulis Lasem Industry. The research result shows that the  effective and appropriate supply model chain for Batik Tulis Lasem Industrialist  is basic material supply model and no agent distribution product